Persistently Elevated Levels of von Willebrand Factor Antigen in HIV Infection - Aukrust, P.; Bjørnsen, S.; Lunden, B.; Otterdal, K.; Ng, E. C.; Ameln, W.; Ueland, T.; Müller, F.; Solum, N. O.; Brosstad, F.; Frøland, S. S. (Thrombosis and Haemostasis, 2000)
Levels of circulating von Willebrand factor (vWf) antigen are thought to reflect endothelial involvement in various disorders. In the present study we found markedly elevated plasma levels of vWf in HIV-infected patients demonstrated on both cross-sectional and longitudinal testing. Notably, we found that a persistent rise in vWf antigen was associated with progression of HIV-related disease. This elevation of vWf antigen represented functionally normal vWf as evaluated by plasma FVIII, ristocetin cofactor assay and vWf multimer analyses. While HIV-infected patients showed enhanced platelet activation, platelets did not contribute substantially to the increased vWf levels. The high vWf levels were significantly correlated with high viral load, and during HAART, the pronounced decline in HIV RNA levels was accompanied by a corresponding decrease in vWf. The persistent elevation of functionally normal vWf during HIV infection, most probably reflecting a persistent endothelial cell activation, may have an important role in the pathogenesis of HIV infection.
Keywords: von Willebrand factor; HIV infection; endothelial cells; platelets; highly active antiretroviral therapy